Growth, Antigenicity, and Immunogenicity of SARS-CoV-2 Spike Variants Revealed by a Live rVSV-SARS-CoV-2 Virus - Ding, Limin S.; Zhang, Yuhang; Wen, Dan; Ma, Jianbo; Yuan, Hao; Li, Hongyue; Duo, Shuguang; Yuan, Fei; Zhang, Yong E.; Zheng, Aihua (Frontiers in Medicine, 2022)
SARS-CoV-2 is an emerging coronavirus threatening human health and the economy worldwide. As an RNA virus, variants emerge during the pandemic and potentially influence the efficacy of the anti-viral drugs and vaccines. Eight spike variants harboring highly recurrent mutations were selected and introduced into a replication-competent recombinant VSV in place of the original G protein (rVSV-SARS-CoV-2). The resulting mutant viruses displayed similar growth curves in vitro as the wild-type virus and could be neutralized by sera from convalescent COVID-19 patients. Several variants, especially Beta strain, showed resistance to human neutralizing monoclonal antibodies targeting the receptor-binding domain (RBD). A single dose of rVSV-SARS-CoV-2 Beta variant could elicit enhanced and broad-spectrum neutralizing antibody responses in human ACE2 knock-in mice, while other mutants generated antibody levels comparable to the wild-type. Therefore, our results will be of value to the development of next-generation vaccines and therapeutic antibodies.